Lexicographical Practice and Lexicological Research: The Case of Shangani in Zimbabwe - Mabaso, Peniah (Lexikos, 2007)
Abstract: The article outlines the contribution of ALRI towards the development of the minority languages in Zimbabwe, with special reference to Shangani. After a description of the status of Shangani, a brief summary of the Zimbabwean language use policy is given. The challenges for the development of lexicographical practice and lexicological research are discussed with regard to a minority language that has been marginalized for a long time. After the consideration of the kind of dictionary planned for Shangani in accordance with the user profile, the role of a dictionary in codifying and harmonizing a language is stressed. Except for contributing to the orthographic development of a language, lexicography also forms the basis for the furtherance of literacy in a community.Keywords: ALRI, MINORITY LANGUAGES, MARGINALIZED LANGUAGES, LEXICO-GRAPHICAL PRACTICE, LEXICOLOGICAL RESEARCH, DICTIONARY, TARGET USERS, SHANGANIOpsomming: Leksikografiese praktyk en leksikologiese navorsing: Die geval van Sjangani in Zimbabwe. Die artikel skets die bydrae van ALRI tot die ontwik-keling van die minderheidstale in Zimbabwe, met spesiale verwysing na Sjangani. Na 'n beskry-wing van die status van Sjangani, word 'n kort opsomming van die Zimbabwiese taalgebruiks-beleid gegee. Die uitdagings vir die ontwikkeling van leksikografiese beleid en leksikologiese navorsing word bespreek met betrekking tot 'n minderheidstaal wat vir 'n lang tyd gemarginaliseer is. Na 'n beskouing van die soort woordeboek wat in ooreenstemming met die gebruikersprofiel vir Sjangani beplan word, word die rol van 'n woordeboek vir die kodifisering en harmonisering van 'n taal beklemtoon. Behalwe dat dit bydra tot die ortografiese ontwikkeling van 'n taal, vorm leksi-kografie ook die basis vir die bevordering van geletterdheid in 'n gemeenskap.Sleutelwoorde: ALRI, MINDERHEIDSTALE, GEMARGINALISEERDE TALE, LEKSIKO-GRAFIESE PRAKTYK, LEKSIKOLOGIESE NAVORSING, WOORDEBOEK, TEIKENGEBRUI-KERS, SJANGANI